Family Communication in Modern Islamic Communities (The Miracle of the Qur'an in the Digital Era to Address the Fragility of Marital Harmony) - Delima, Wirda (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2024)
This study aims to explore how family communication within Muslim communities in the modern era can be strengthened by examining the wonders of the Qur'an. The research method used is descriptive qualitative with a natural phenomenological approach. Data were collected through the review of various publications and the observation of phenomena both directly and indirectly, which were then analyzed to draw conclusions. The findings indicate that the Qur'an plays a crucial role as a solution and guide in facing the advancements of the modern era and the world of technology. The main findings include: 1) The importance of putting away devices when gathering with family, 2) Establishing good communication, and 3) Using the Qur'an as a family guide. Through this research, it is highlighted that good communication is essential to deepen loving relationships within the family. Without effective communication, the atmosphere within the family becomes chaotic and disorganized, making it difficult to achieve a harmonious family. Many family problems in the modern era stem from family members being preoccupied with their devices, lack of commitment, and poor communication, which distances the family from the guidance of the Qur'an.